2005
DOI: 10.1091/mbc.e04-07-0585
|View full text |Cite
|
Sign up to set email alerts
|

XGef Mediates Early CPEB Phosphorylation duringXenopusOocyte Meiotic Maturation

Abstract: Polyadenylation-induced translation is an important regulatory mechanism during metazoan development. During Xenopus oocyte meiotic progression, polyadenylation-induced translation is regulated by CPEB, which is activated by phosphorylation. XGef, a guanine exchange factor, is a CPEB-interacting protein involved in the early steps of progesterone-stimulated oocyte maturation. We find that XGef influences early oocyte maturation by directly influencing CPEB function. XGef and CPEB interact during oogenesis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 50 publications
0
28
0
Order By: Relevance
“…Overexpression in oocytes of a guaninenucleotide-exchange-deficient version of XGef that is unable to activate small GTPases does not enhance early CPEB phosphorylation, as observed upon overexpression of wildtype XGef (Martinez et al, 2005). We therefore suspected that XGef influences early CPEB phosphorylation through activation of a Rho-family GTPase.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Overexpression in oocytes of a guaninenucleotide-exchange-deficient version of XGef that is unable to activate small GTPases does not enhance early CPEB phosphorylation, as observed upon overexpression of wildtype XGef (Martinez et al, 2005). We therefore suspected that XGef influences early CPEB phosphorylation through activation of a Rho-family GTPase.…”
Section: Resultsmentioning
confidence: 90%
“…When XGef is overexpressed in Xenopus oocytes, we observe an increase in the level of phosphorylated CPEB during early meiosis, earlier elongation of poly (A) tails on Mos mRNA, earlier accumulation of Mos protein and an acceleration of meiotic progression by ~25% (Martinez et al, 2005;Reverte et al, 2003). A version of XGef that has very reduced interaction with CPEB functions in a dominantnegative manner and substantially impairs these events.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…GEF activity of XGef is required for Mos synthesis. In addition, interaction between XGef is responsible for an increase in CPEB phosphorylation during oocyte maturation, which is important for CPEB activation (Martinez et al 2005). Further studies have shown that MAPK interacts with XGef and acts as a kinase of CPEB on Thr-22, Thr-164, Ser-184, and Ser-248 (Keady et al 2007).…”
Section: Xgefmentioning
confidence: 99%
“…Progesterone causes a series of reactions culminating in the translation of the RNA for the protein Pp39mos, laying till that point inactive in the cytoplasm. This happens because a protein called CEBP gets phosphorylated by the effect of the protein Xgef (Martinez et al 2005) and binds to a sequence of this RNA (Howard et al 1999;Dickson et al 1999;Reverte et al 2003), made by 6 U and 1 A, causing the RNA polyadenylation (Hake & Richter 1994;Sheets et al 1994;Barkoff et al 1998) in 3'. At the same time the cap at its 5' end becomes methylated (Kuge et al 1998).…”
Section: Xenopusmentioning
confidence: 99%